2008
DOI: 10.1590/s0100-879x2008005000022
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein CIII polymorphism and triglyceride levels of a Japanese population living in Southern Brazil

Abstract: Apolipoprotein CIII (apo-CIII) participates in the regulation of triglyceride-rich lipoprotein metabolism. Several polymorphic sites have been detected within and around the apo-CIII gene. Here, we examined the relationship between apo-CIII Sst I polymorphism (CC, CG, GG genotypes) and plasma triglyceride (TG) levels in a group of 159 Japanese individuals living in Southern Brazil. The sample was divided into a group of Japanese descendants (N = 51) with high TG (HTG; >200 mg/dL) and a group of Japanese descen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
(26 reference statements)
1
9
0
5
Order By: Relevance
“…Previous cohort studies, as well as case-control and familial studies have shown significant association between the rare allele of the polymorphic Sst I site (3238G) and higher plasma TG levels [16-53] and CAD [53-62]. This association has been reported in studies carried out with Caucasians, Chinese, Mayans, Japanese (living in Japan or living in Southern Brazil), Koreans, Arabs, and Asian Indians [27,49,55,69,70]. However, several reports failed to find a significant genetic effect on TG concentrations [71-73].…”
Section: Discussionmentioning
confidence: 84%
“…Previous cohort studies, as well as case-control and familial studies have shown significant association between the rare allele of the polymorphic Sst I site (3238G) and higher plasma TG levels [16-53] and CAD [53-62]. This association has been reported in studies carried out with Caucasians, Chinese, Mayans, Japanese (living in Japan or living in Southern Brazil), Koreans, Arabs, and Asian Indians [27,49,55,69,70]. However, several reports failed to find a significant genetic effect on TG concentrations [71-73].…”
Section: Discussionmentioning
confidence: 84%
“…Os fragmentos originados da digestão enzimática foram observados em gel de agarose a 2%. Foram classificados como alelo G os fragmentos que apresentaram um tamanho de 269 pares de bases (pb) e 159 pb e como alelo C os fragmentos que apresentaram um tamanho de 428 pb 10 .…”
Section: Metodologiaunclassified
“…As lipoproteínas de baixa densidade (LDLs) são consideradas as principais transportadoras plasmáticas de colesterol a todos os tecidos, sendo que sua absorção ocorre predominantemente no fígado (75%), no tecido adiposo e nas glândulas adrenais 10 . A HDL possui inúmeras ações protetoras, como proteção antioxidante, mediação do fluxo de colesterol, inibição da expressão de moléculas de adesão celular, ativação de leucócitos, indução da produção de óxido nítrico (NO), regulação da coagulação sanguínea e modulação da atividade plaquetária 11 .…”
Section: Introductionunclassified
See 2 more Smart Citations